1997
DOI: 10.1021/jp971331+
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Diffraction and Molecular Dynamics Study of Liquid Benzene and Its Fluorinated Derivatives as a Function of Temperature

Abstract: The study of the local translational and orientational ordering in benzene (C6H6), 1,3,5-trifluorobenzene (C6H3F3) and hexafluorobenzene (C6F6) neat liquids has been performed along their liquid−vapor coexistence curve between the melting point and the boiling point combining neutron diffraction experiments and molecular dynamics simulation. Both experiment and simulation show that the local ordering is only very slightly affected in the temperature range investigated. The analysis of the results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
100
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(123 citation statements)
references
References 42 publications
22
100
1
Order By: Relevance
“…These different results may arise from the fact that the previous X-ray scattering studies accepted the quasi-lattice structure for the liquid based on the crystal structure of benzene. A slightly favourable presence of the parallel and perpendicular configurations was indicated by the molecular dynamics simulation [10,11]. However, our result suggests that the parallel (stacked) configuration is not the major one and the perpendicular configuration exists predominantly.…”
Section: Structure Of Liquid Benzenementioning
confidence: 46%
See 2 more Smart Citations
“…These different results may arise from the fact that the previous X-ray scattering studies accepted the quasi-lattice structure for the liquid based on the crystal structure of benzene. A slightly favourable presence of the parallel and perpendicular configurations was indicated by the molecular dynamics simulation [10,11]. However, our result suggests that the parallel (stacked) configuration is not the major one and the perpendicular configuration exists predominantly.…”
Section: Structure Of Liquid Benzenementioning
confidence: 46%
“…On the other hand, the result by a pulsed neutron total scattering experiment at room temperature supported the T configuration in which two molecules are inclined at about 73 [9]. On the contrary to the above observations, analyses of neutron scattering data from the liquid to the supercritical states with the aid of the molecular dynamics simulation revealed that there is no preferential orientational ordering of the neighbouring molecules on average at ambient conditions although the parallel and perpendicular configurations are slightly favoured [10,11]. Thus, much different results on the structure of liquid benzene have been reported so far.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…That is why the average C-C-C-H torsional energy is the same as K 3 Structural properties. The radial distribution function, g(r), is defined as (14) where ρ 0 is the bulk density, N(r, ∆r) is the number of molecules in a shell which is between r − ∆r/2 and r + ∆r/2 from the center of a molecule with ∆r = 0.005 nm, V(r, ∆r) is the volume of the shell, and <···> indicates the isothermal-isobaric ensemble (NpT) average. The center of mass g(r) of liquid benzene, toluene, and p-xylene at 283.15, 303.15, 323.15, and 343.15 K are shown in Figures 1-3, respectively, and the site-site g C-C (r) of liquid benzene, toluene, and p- xylene at 283.15 K is also shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The computed values of D s were corrected for system size effects using the hydrodynamic model of Yeh and Hummer 78 of a particle surrounded by a solvent with a viscosity, η, (4) Isothermal compressibilities were calculated from (5) where V is the volume, 〈δV 2 〉 are volume fluctuations and K B is the Boltzmann's constant.…”
Section: Methodsmentioning
confidence: 99%